Ion conduction mechanism and super capacitor performance of polymer electrolyte incorporated with ionic liquid - Zakariya'u, Ibrahim; Nasir, Sehrish; Rawat, Neelam; Kathuria, Shubham; Diantor, Markus; Noor, I. M.; Singh, Pramod Kumar (John Wiley and Sons, 2025)
In the present work, highly conducting polymer electrolyte films are prepared by integrating Polyvinyl-pyrrolidone (PVP) with sodium iodide (NaI) salt. To further improve performance, different concentrations of an ionic liquid, 1-ethyl-3-methylimidazolium thiocyanate, were added to the optimized polymer matrix containing salt through the solution casting method. Experiments with complex impedance spectroscopy identified conductivity, and the electrochemical stability window was measured using linear sweep voltammetry. The number of charge carriers (Tion) is studied using Wagner's DC polarization method. A notable increase in conductivity was recorded after the addition of the ionic liquid to the maximum conductive polymer-salt system. Fourier transform infrared (FTIR) spectroscopy validated the composite structure and the complexation within the matrix. Additionally, polarized optical microscopy indicated a decrease in crystallinity and an increase in amorphous content because of interaction with both the salt and the ionic liquid. The resulting highly conductive polymer electrolyte, achieved by combining the salt and ionic liquid, and previously reported activated carbon-based electrodes are utilized to fabricate an electrical double-layer capacitor (EDLC). The EDLC cell is further studied using various electrochemical tools such as EIS, CV, and GCD.